2009
DOI: 10.1104/pp.109.149351
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Acclimation of Photosynthesis Increases Plant Fitness in Changing Environments      

Abstract: Plants growing in different environments develop with different photosynthetic capacities—developmental acclimation of photosynthesis. It is also possible for fully developed leaves to change their photosynthetic capacity—dynamic acclimation. The importance of acclimation has not previously been demonstrated. Here, we show that developmental and dynamic acclimation are distinct processes. Furthermore, we demonstrate that dynamic acclimation plays an important role in increasing the fitness of plants in natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
235
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(259 citation statements)
references
References 29 publications
15
235
3
2
Order By: Relevance
“…We previously demonstrated that developmental and dynamic acclimation are, to some extent, distinct processes in Arabidopsis thaliana (Athanasiou et al . 2010). …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that developmental and dynamic acclimation are, to some extent, distinct processes in Arabidopsis thaliana (Athanasiou et al . 2010). …”
Section: Introductionmentioning
confidence: 99%
“…2010). Arabidopsis accession Wassilewskija‐4 (Ws‐4) shows a strong dynamic acclimation of photosynthetic capacity, increasing P max by up to 40% when moved from a low to a higher irradiance and this ability to acclimate dynamically plays a major role in determining plant's fitness in naturally fluctuating environments (Athanasiou et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations